Pengaruh Physical Evidence, Store Atmosphere dan Harga terhadap Kepuasan Konsumen di Muaro Terrace Cafe & Resto Hotel Truntum Kota Padang - Qawiema Nashita; Rian Surenda (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the phenomenon found by researchers on consumer satisfaction related to physical evidence, store atmosphere and price of Muaro Terrace Cafe & Resto. This research is quantitative in nature and uses a causal associative approach through the survey method. The population of this study were consumers at Muaro Terrace Cafe & Resto with purposive sampling method obtained a sample of 150 respondents. The results of this study are the average respondent on the physical evidence variable 82.0% with good criteria, the store atmosphere variable 81.5% with good criteria, the price variable 80.5% with a good category then concluded that the average respondent of the consumer satisfaction variable was 82.3% in a good category. When F count is 161.216 with a sig of 0.000 <0.05 obtained from the multiple linear regression test results, the regression can be applied. Shows physical evidence, store atmosphere and price have an important impact on customer satisfaction. The Adjust R Square value is 0.763, which indicates that although additional factors not covered in this study affect 23.7% of customer satisfaction at Muaro Terrace Cafe & Resto, the remaining 76.3% is determined by the variables of physical evidence, store atmosphere and price.